Sexual dimorphism in the long-term stability (10 years) of skeletal Class III treatment - Natalia Tejedor; Conchita Martín; José Antonio Alarcón; María Dolores Oteo-Calatayud; Juan Carlos Palma-Fernández (SpringerOpen, 2021)
Abstract Background Class III malocclusion is associated with high sexual dimorphism, especially in individuals older than 13 years of age, with significant differences in growth between males and females during the pubertal and postpubertal stages, and in adulthood. The aim of this research was to examine differences between males and females in long-term stability (10 years) of treatment for skeletal Class III malocclusion. Methods Thirty patients (15 males and 15 females) with skeletal Class III malocclusion, who had been treated with rapid maxillary expansion (RME) combined with face mask protraction followed by fixed appliances, were selected sequentially. Thirty patients (15 males and 15 females) with skeletal Class I and mesofacial patterns treated only with fixed appliances for dental problems served as the control group. Differences between groups and sexes were evaluated using lateral cephalograms taken at the start of treatment (T0), immediately after the end of treatment (T1), and after 10 years (T2). The long-term treatment success rate was calculated. Results Ten years after Class III treatment, overjet and overbite relapse occurred similarly in females (− 0.68 ± 0.7 mm; − 0.38 ± 0.75 mm, respectively) and males (− 1.09 ± 1.47 mm; − 0.64 ± 0.9 mm, respectively); the ANB angle and Wits appraisal became significantly more negative in males (− 1.37 ± 1.06°; − 2.7 ± 2.53 mm) than in females (− 0.18 ± 1.26°; − 0.46 ± 1.94 mm). The success rate was 73.3% in males and 80% in females. Conclusions Significant differences in the long-term stability of Class III treatment outcomes have been found between males and females, with a larger skeletal Class III relapse and lower long-term success rates in males.